2007
DOI: 10.1111/j.1365-2788.2006.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary approach to the management of individuals with fragile X syndrome

Abstract: Frequency of psychiatric diagnoses made with DSM-IV were in parallel to those reported in the literature. Comorbidity of seizures and psychiatric disorders was noteworthy. The percentage of 'high-functioning' full mutation males supports the previous observations. Ear nose and throat and eye examination revealed remarkably lower prevalence of abnormal findings than reported. MVP was slightly less frequent compared with the single study in the literature. Age at the time of examination had an effect on the outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…showing a stronger phenotype and a greater degree of intellectual disability than females (Alanay et al, 2007). The behavioral phenotype includes language impairment, social anxiety, gaze aversion, repetitive and self-injurious behavior (see Hagermann & Hagermann, 2002).…”
Section: Assessment Of Social Anxiety Inmentioning
confidence: 99%
“…showing a stronger phenotype and a greater degree of intellectual disability than females (Alanay et al, 2007). The behavioral phenotype includes language impairment, social anxiety, gaze aversion, repetitive and self-injurious behavior (see Hagermann & Hagermann, 2002).…”
Section: Assessment Of Social Anxiety Inmentioning
confidence: 99%
“…60,61 Earlier studies reported that the prevalence of strabismus in boys with FXS ranged from 27% to 57%. 8,[56][57][58] Later prospective studies reported the prevalence to range from 4.4% 16 to 8% 55 of boys with FXS. In the FXCRC Database, the prevalence of strabismus was higher overall (16.4%) and particularly in boys (17.5%) ( Table 1).…”
Section: Ocular Disordersmentioning
confidence: 99%
“…16,55,56 Children with FXS, many of whom need glasses, are reported to have a high prevalence of refractive errors, ranging from 13% to 17%. 16,55 In earlier studies, there were 59% with hyperopia, 17% with myopia, and 22% to 40% with astigmatism.…”
Section: Ocular Disordersmentioning
confidence: 99%
See 2 more Smart Citations